Pleiotropic effects of PipX, PipY, or RelQ overexpression on growth, cell size, photosynthesis, and polyphosphate accumulation in the cyanobacterium Synechococcus elongatus PCC7942 - Llop, Antonio; Labella, Jose I.; Borisova, Marina; Forchhammer, Karl; Selim, Khaled A.; Contreras, Asunción (Frontiers in Microbiology, 2023)
The cyanobacterial protein PipY belongs to the Pyridoxal phosphate (PLP)-binding proteins (PLPBP/COG0325) family of pyridoxal-phosphate binding proteins, which are represented in all three domains of life. These proteins share a high degree of sequence conservation, appear to have purely regulatory functions, and are involved in the homeostasis of vitamin B6 vitamers and amino/keto acids. Intriguingly, the genomic context of the pipY gene in cyanobacteria connects PipY with PipX, a protein involved in signalling the intracellular energy status and carbon-to-nitrogen balance. PipX regulates its cellular targets via protein-protein interactions. These targets include the PII signaling protein, the ribosome assembly GTPase EngA and the transcriptional regulators NtcA and PlmA. PipX is thus involved in the transmission of multiple signals that are relevant for metabolic homeostasis and stress responses in cyanobacteria, but the exact function of PipY is still elusive. Preliminary data indicated that PipY might also be involved in signalling pathways related to the stringent stress response, a pathway that can be induced in the unicellular cyanobacterium Synechococcus elongatus PCC7942 by overexpression of the (p)ppGpp synthase, RelQ. To get insights into the cellular functions of PipY we performed a comparative study of PipX, PipY or RelQ overexpression in S. elongatus PCC7942. Overexpression of PipY or RelQ caused similar phenotypic responses, such as growth arrest, loss of photosynthetic activity and viability, increased cell size and accumulation of large polyphosphate granules. In contrast, PipX overexpression decreased cell length, indicating that PipX and PipY play antagonistic roles on cell elongation or cell division. Since ppGpp levels were not induced by overexpression of PipY or PipX, it is apparent that the production of polyphosphate in cyanobacteria does not require induction of the stringent response.